Free radical oxidation: a pathophysiologist’s view - L. I. Kolesnikova; M. A. Darenskaya; S. I. Kolesnikov (Бюллетень сибирской медицины, 2018)
Significant progress in the field of free radical biology and medicine since the middle of the century has been made. Subsequently, the spectrum of diseases and pathological states believed to be associated with free radicals significantly has been expanded. At present, the development of oxidative stress molecularcellular mechanisms investigations is extremely topical for medical science because it involves in a number of pathologies, including social-significance disorders .The important role of the lipid peroxidation (LPO) system and deficiency of antioxidant defense (AOD) factors in general pathological processes has been proved by authors and their assistants in the laboratories of the Institute of Clinical and Experimental Medicine of Siberian Branch of the Russian Academy of Medical Sciences (Novosibirsk), since 1972. A list of these processes: cold and toxic stress, tumor growth, inflammation, physiologic and pathologic pregnancies (including experimental models). In fact the first clinical investigations were not only in the USSR, but also in the whole world. Several patents proved this.In the experiments on rodents, the phenomenon of imprinting on the offspring’s LPO and drug metabolism after LPO inducing toxicants action during pregnancy was discovered.The research series continued at the Scientific Centre for Family Health and Human Reproduction Problems (Irkutsk). Technology for oxidative stress evaluation and the use of antioxidants in the complex therapy of complicated and uncomplicated pregnancy, reproductive disorders in men and women, sleep disorders, sociallysignificant diseases, pediatric practice were created here. The analysis of lipid peroxidation changes during the physiological development of the reproductive function performed. The gender and ethnic dependence of lipid peroxidation was noted. Ethno-specific changes in the LPO-AOD system among the representatives of the Buryat ethnic group at different pathologic conditions (diabetes mellitus type 1, essential arterial hypertension, complicated pregnancy, endocrine infertility, endometriosis, male infertility), were revealed. The LPO-AOD was used to define “relative ethnic norm” for Buryat ethnic group. The “specificity” of features of nonspecific process of free radical oxidation in different pathologic situations was postulated. It is very important for personalized diagnosis, prevention and treatment.